Physical properties of the rubberized interlocking masonry brick - Al-Fakih, A. (IAEME Publication, 2018)
Scrap tires consider the current major discarded waste which results in major environmental issues. At the same time, utilization of earth based materials such as clay, sand (soil), and cement in the production of masonry units brought about resource depletion and environmental degradation. Rubberized interlocking bricks was produced by incorporating 10 of crumb rubber and 56 by volume to replace the fine aggregate and cement, respectively. The physical characteristics of the developed brick unit was investigated including dimension tolerance, density, net volume, net area and water absorption. The result revealed that a rubberized interlocking brick gave more suitable results that comply with the requirements limits of standards codes. 250 mm length, 125 mm width, and 105 mm height was confirmed to be the size of the developed brick and density of 1890 kg/m3 which classified as medium weight masonry brick. Â© IAEME Publication.